DESIGN OF INFORMATION TECHNOLOGY GOVERNANCE IN DOMAIN EDM BASED ON COBIT 5 IN RS. PHC - Arizky Vebby Widardo; Haryanto Tanuwijaya; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2019)
PHC hospitals are type B hospitals in Surabaya that implement IT to provide effectiveness in business processes. Currently the need for IT services is increasing and IT is increasingly sophisticated, this makes PHC hospitals continue to improve IT quality. The authorized part in IT development is the board level for evaluating, directing and monitoring IT. But at this time in the hospital there were no risk assessments, IT policies, monitoring of IT risk management, determination of IT standards and IT HR management, so that the implementation was not in accordance with the needs and caused re-changes in implementation requiring time, effort and costs for research .In solving the problem solving there needs to be an IT governance that focuses on board level, the framework that can be used is CobIT5, which has support for managing board level parts, namely Evaluation, Direct Monitoring (EDM),The results of this information technology governance design in the form of 33 recommendations for achieving capability level 1. 33 These recommendations are obtained from output work products that include 5 EDM domains that can ensure having a governance framework, IT benefits that support business, risk optimization, resource optimization and stakeholder transparency.Keywords: Information Technology Governance, Board Level, CobIT5, EDM.